A Comprehensive Approach to Facility Management in Enhancing Physical Fitness and Sports Performance - Ishak, Muhammad; Awaluddin, Awaluddin; Hasanuddin, M. Imran (Indonesian Journal of Sport Management, 2025)
This study investigates the impact of comprehensive facility management on the physical fitness and sports performance of student-athletes at the South Sulawesi Sports School (PPLP). Using a mixed-methods approach, data were collected from 30 athletes, five coaches, and three facility managers across four sports disciplines: athletics, pencak silat, karate, and sepak takraw. Quantitative assessments included physical performance evaluations—speed, agility, endurance, and strength—while qualitative insights were drawn from interviews, observations, and document analysis. The findings revealed that only 62% of the training facilities met national standards for safety and maintenance. Key issues included inadequate lighting, worn-out flooring, and limited equipment availability. Satisfaction surveys indicated that only 40% of athletes rated the training facilities “satisfactory” or better. Physical test results showed a clear correlation between facility quality and performance: athletes with access to well-maintained facilities recorded faster sprint times (average 3.21s vs. 3.48s) and higher agility scores (16.4s vs. 17.2s). Thematic analysis of stakeholder interviews revealed three main barriers: lack of maintenance budgeting, inconsistent scheduling, and psychological impacts of poor facility quality. A Pearson correlation analysis confirmed a moderate positive relationship (r = 0.54, p < 0.05) between facility conditions and athlete performance. This study contributes a novel integrative framework combining physical assessment and stakeholder perceptions to evaluate the effectiveness of sports infrastructure. The results underscore the strategic role of facility management in optimizing athlete development and provide a model for evidence-based policy formulation in regional sports institutions.